Kinase-mediated changes in nucleosome conformation trigger chromatin decondensation via poly(ADP-ribosyl)ation. - Thomas, C.J.; Kotova, E.; Andrake, M.; Adolf-Bryfogle, J.; Glaser, R.; Regnard, C.; Tulin, A.V. (Molecular Cell, 2014)
Dynamically controlled posttranslational modifications of nucleosomal histones alter chromatin condensation to regulate transcriptional activation. We report that a nuclear tandem kinase, JIL-1, controls gene expression by activating poly(ADP-ribose) polymerase-1 (PARP-1). JIL-1 phosphorylates the C terminus of the H2Av histone variant, which stimulates PARP-1 enzymatic activity in the surrounding chromatin, leading to further modification of histones and chromatin loosening. The H2Av nucleosome has a higher surface representation of PARP-1 binding patch, consisting of H3 and H4 epitopes. Phosphorylation of H2Av by JIL-1 restructures this surface patch, leading to activation of PARP-1. Exposure of Val61 and Leu23 of the H4 histone is critical for PARP-1 binding on nucleosome and PARP-1 activation following H2Av phosphorylation. We propose that chromatin loosening and associated initiation of gene expression is activated by phosphorylation of H2Av in a nucleosome positioned in promoter regions of PARP-1-dependent genes.